Study of Historical and Cultural Tourism in Siulak, Kerinci Regency Jambi - Apdelmi Apdelmi (Diakronika, 2018)
Kerinci Regency is located at the West of Jambi Province. The regency has the highest number of tourism in Jambi province, according to the Department of Tourism and Culture of Jambi Province in 2014.Kerinci was ranked first in terms of the number of Tourism and 20 of them were historical/cultural tourism. Kerinci has a great opportunity in the development of the historical tourism sector. However, at present the attention to the historical tourism sector is still lacking. This research uses qualitative descriptive method where data is obtained from interviews and documentation. The results showed that several places in Siulak have the potential to be developed as historical tourism objects, but due to the lack of maintenance, it is necessary to take corrective steps to make these objects become historical tourism.